Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Inap Rumah Sakit Umum Daerah Kayuagung - Anton Trianto; Muhammad Deni; Marita Pratisila; Nanda Revita (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of service quality on inpatient satisfaction at the Kayuagung Regional General Hospital (RSUD). Respondents who became the object of research were inpatients at the Kayuagung Hospital who had been allowed to go home or do outpatient care. The sampling technique used was simple random sampling with the number of samples calculated using the Slovin formula and a sample of 85 respondents was taken. The data used is primary data collected through a questionnaire instrument. The analysis technique used is correlation analysis and simple linear regression. Based on the results of calculations in regression analysis and hypothesis testing (t test) it was found that the quality of rehabilitation services had a positive and significant effect on the satisfaction of inpatients at the Kayuagung Hospital. Judging from the value of the coefficient of determination (R-Square) it was found that the variable quality of rehabilitation services had an influence of 53.8 percentin shaping the satisfaction variable of inpatients at the Kayuagung Hospital, while the remaining 46.2 percent was determined by other variables outside the regression model. Based on the descriptive analysis of the percentage of respondents' answers to the questionnaire, it was concluded that patient satisfaction was dominated by the influence of the responsiveness indicators of medical officers who were considered alert and fast in serving inpatients at the Kayuagung Hospital.